PENAL ACCOUNTABILITY OF SPENDING USER OFFICER/ SPENDING USER AUTHORITY (SUO/ SUA) IN THE GOVERNMENT PROCUREMENT OF GOODS AND SERVICES - M. Sofian Assaori (Fakultas Hukum Universitas Mataram, 2015)
This research is a normative research, consider that this research heading off from statute analysis on the type of corruption. Corruption penal accountability and the position or personal indication of faults over government’s goods and services procurement, this research applying statutes, conceptual and case approach. According to research result, we may conclude that the corruption type that potentially conducted by SUO/ SUA are: against the law act, abuse of authority, bribes and gratification. Furthermore, personal faults generally may indicated by the containing of unlawful act (fault) in his personal deed, capable of being responsible, the absence of forgiveness and justification excuse. While particular indication such as unlawful act, abuse of authority and obligation neglected. Thereafter, indications of position fault are arbitrary of authority, violation on good governance principles and mal-procedure/ administration. Keywords: accountability, fault, corruption.